2021
DOI: 10.22219/raden.v1i2.18911
|View full text |Cite
|
Sign up to set email alerts
|

Digital comics learning media for high school on the human excretory system concept

Abstract: Based on the preliminary analysis, one of the things needed in learning is a learning media that describes the material clearly, briefly, easily understood, and fulfills offline and online learning. This research aims to develop a digital comic learning media on the concept of the human excretory system. This study uses the R&D (Research and Development) method with the ADDIE model. The instruments in this study include a validation questionnaire, practicality test sheets, readability questionnaire, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Education is the main vehicle for preparing quality human resources (Adam, 2022;Agustini et al, 2021;Arifin et al, 2021;Muhlasin et al, 2022;Muninda et al, 2021;Octaviana et al, 2021;Prasetyo et al, 2022;Rohmania et al, 2022;Sari et al, 2021;Varisa & Fikri, 2022), including in preparing careers according to the wishes and aspirations of children. Activities related to career information services can be carried out in various ways, one of them is through career day activities (Muriyawati & Rohmah, 2016).…”
Section: Article Historymentioning
confidence: 99%
“…Education is the main vehicle for preparing quality human resources (Adam, 2022;Agustini et al, 2021;Arifin et al, 2021;Muhlasin et al, 2022;Muninda et al, 2021;Octaviana et al, 2021;Prasetyo et al, 2022;Rohmania et al, 2022;Sari et al, 2021;Varisa & Fikri, 2022), including in preparing careers according to the wishes and aspirations of children. Activities related to career information services can be carried out in various ways, one of them is through career day activities (Muriyawati & Rohmah, 2016).…”
Section: Article Historymentioning
confidence: 99%
“…Meningkatkan hasil belajar dan agar siswa lebih dapat memahami materi yang disampaikan dalam proses pembelajaran pada mata pelajaran IPA, maka guru harus berusaha untuk mencari strategi mengajar dan pemilihan media yang tepat, sehingga dapat mensiasati agar siswa lebih aktif dan focus waktu kegiatan pembelajaran berlangsung. Berbagai media pembelajaran banyak dikembangkan oleh peneliti untuk membuat pembelajaran lebih menarik, seperti multimedia (Arifin et al, 2022;Dhanil & Mufit, 2021;Husein et al, 2015), komik (Agatha et al, 2017;Agustini et al, 2021;Octaviana et al, 2021), maupun modul online (Pratono et al, 2018;Rohmania et al, 2022). Salah satu media yang sederhana namun bisa memberikan motivasi pada siswa adalah media video.…”
Section: Pendahuluanunclassified
“…While, the reproductive system material requires learning media to improve students' understanding and learning outcomes. Learning media is necessary for delivering this material as it involves internal body processes that cannot be directly observed, which makes it challenging for students (Agustini et al, 2021;Ardi et al, 2023;Astatin & Nurcahyo, 2016;Muninda et al, 2021;Prasetyo et al, 2022;Puspita et al, 2017;Syamsurizal et al, 2021). Various studies have shown the effectiveness of different learning media in enhancing students' cognitive learning outcomes in biology subjects related to the reproductive system (Eliana et al, 2022;Ibrahim, 2023;Kurniawan et al, 2018;Panjaitan et al, 2020;Roihana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%